A Study on the University Students’ Speaking Difficulties - Z Zainurrahman; Sumarni Sangaji (Program Studi Pendidikan Bahasa Inggris, STKIP Kie Raha Ternate, 2019)
Speaking difficulty encountered by the students in every level is one of the major issues in the teaching of EFL. Many researchers reported that the factors are ranged from linguistic domain to psychology. Many experts wrote textbooks and articles to discuss this issue in hoping that the teaching of English speaking in particular can achieve satisfactory result. However, speaking difficulties are found from time to time and this is not because of the material or the teaching strategies. Although the role of the teachers is important, but individual issue of the student also needs to be taken into account. This qualitative research involved 14 university students and they were taken randomly from a university. By using performance test evaluated with a speaking rubric, it has been found that the students’ grammar knowledge (linguistic domain) was extremely low. However, data from interview, which has been condensed into some keywords, revealed that the students’ performance in speaking activity has been affected by their psychological problem like hesitance and low of self-esteem. Moreover, the finding showed that vocabulary mastery played important role in speaking activity. Psychological reason and vocabulary mastery are two main issues discovered through this research.